2017
DOI: 10.7150/ijms.18059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C-reactive protein on the expression of matrix metalloproteinases and their inhibitors via Fcγ receptors on 3T3-L1 adipocytes

Abstract: The association between obesity and inflammation is well documented in epidemiological studies. Proteolysis of extracellular matrix (ECM) proteins is involved in adipose tissue enlargement, and matrix metalloproteinases (MMPs) collectively cleave all ECM proteins. Here, we examined the effects of C-reactive protein (CRP), an inflammatory biomarker, on the expression of MMPs and tissue inhibitors of metalloproteinases (TIMPs), which are natural inhibitors of MMPs, in adipocyte-differentiated 3T3-L1 cells. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…According to the literature, MMP-3 could also be related to low-grade chronic inflammation in obesity. In line with this, Nakai et al [ 32 ] found that CRP, which is a low-grade systemic inflammation marker, induced MMP-1, MMP-3, and MMP-9 expression in adipocyte-differentiated 3T3-L1 cells. Our study provides, however, no significant association between the investigated polymorphisms and hs-CRP levels.…”
Section: Discussionmentioning
confidence: 72%
“…According to the literature, MMP-3 could also be related to low-grade chronic inflammation in obesity. In line with this, Nakai et al [ 32 ] found that CRP, which is a low-grade systemic inflammation marker, induced MMP-1, MMP-3, and MMP-9 expression in adipocyte-differentiated 3T3-L1 cells. Our study provides, however, no significant association between the investigated polymorphisms and hs-CRP levels.…”
Section: Discussionmentioning
confidence: 72%
“…Another mechanism involved oral bacteria. Nakai et al [31] suggested that obese individuals might have different oral bacteria than normal-weight individuals, which could contribute to the development of periodontitis. In vitro studies have shown that stimulation of adipocytes with C-reactive protein and inflammatory cytokines promotes adipocyte differentiation and increases the production of mature proteases such as matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, periodontal disease is considered a chronic disease that spreads mildly, but systemically [32,33]. In an in vitro study, stimulation of adipocytes with CRP and inflammatory cytokines led to enhanced differentiation of adipocytes and elevated production of maturation-promoting proteinases such as matrix metalloproteinases [34]. Furthermore, induced experimental periodontitis in rats resulted in elevated levels of the monocyte chemotactic factor (monocyte chemoattractant protein-1) in serum and lipids in the liver [35].…”
Section: Discussionmentioning
confidence: 99%